PROSES PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR ALAM (Studi Deskriptif Kualitatif di Kelas I SD Alam Cikeas Bogor) - ANINGSIH, ANINGSIH (JURNAL PENDIDIKAN DASAR, 2012)
The aim of this qualitative research is to understand comprehensively the process of learning mathematics in nature elementary school associated with developmentally appropriate practice (DAP) and studentâs atttitude towards mathematics learning. The research is conducted in the first grade of Cikeas Nature Elementary School located in Puri Cikeas Complex, Nagrak, Gunung Putri, Bogor. The data are collected though participant observation, interview and document study. The data analysis and interpretation indicated: (1) the teacherâs activities in the process of learning mathematics which appropriate to the children development are: explaining concepts by using props, asking open and close questions, teaching by using integrated learning, checking studentsâs works, guiding students, giving positive reinforcement and managing the class; (2) the studentâs activities in the process of learning mathematics which appropriate to the children development are: manipulating props, learning while playing, doing worksheets, learning in group, and peer tutor; (3) the props in the process of learning mathematics are: concrete props, image props and symbol props; (4) the studentâs attitude in the process of learning mathematics are: receiving, responding and valuing.Keywords: the process of learning mathematics, development appropriate practice (DAP), studentâsattitude.